2020
DOI: 10.1186/s12888-020-02881-w
|View full text |Cite
|
Sign up to set email alerts
|

Association of ocular diseases with schizophrenia, bipolar disorder, and major depressive disorder: a retrospective case-control, population-based study

Abstract: Background Psychiatric disorders and ocular neurovascular diseases may share a similar pathophysiological route of vascular structures or neurological changes. The aim of this study is to investigate the association between ocular neurovascular diseases and the risk of major psychiatric disorders. Methods This was a retrospective case–control, population-based study including patients aged ≥20 and were diagnosed between 1997 and 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…There is also emerging evidence that glaucoma is a neurodegenerative condition whose occurrence precedes a range of neurodegenerative disorders [e.g., Alzheimer's disease (81) and mild cognitive impairment (82), as well as indirect evidence for glaucoma-like changes in schizophrenia, including an enlarged cup-to-disc ratio (83) and abnormalities in frequency doubling perimetry reviewed in Almonte et al (84)]. Recent findings also indicate that glaucoma often precedes a diagnosis of schizophrenia, bipolar disorder, or major depression by several years (85). These observations converge to suggest that some of the abnormal visual activity in schizophrenia may be secondary to reduced retinal input to the visual cortex, a hypothesis that received preliminary support in a computational model ( 86).…”
Section: Syndromes Of Visual Hallucinationsmentioning
confidence: 99%
“…There is also emerging evidence that glaucoma is a neurodegenerative condition whose occurrence precedes a range of neurodegenerative disorders [e.g., Alzheimer's disease (81) and mild cognitive impairment (82), as well as indirect evidence for glaucoma-like changes in schizophrenia, including an enlarged cup-to-disc ratio (83) and abnormalities in frequency doubling perimetry reviewed in Almonte et al (84)]. Recent findings also indicate that glaucoma often precedes a diagnosis of schizophrenia, bipolar disorder, or major depression by several years (85). These observations converge to suggest that some of the abnormal visual activity in schizophrenia may be secondary to reduced retinal input to the visual cortex, a hypothesis that received preliminary support in a computational model ( 86).…”
Section: Syndromes Of Visual Hallucinationsmentioning
confidence: 99%
“…The occurrence of ocular diseases was defined as having ≥2 new-onset outpatient diagnoses or any inpatient diagnosis at ophthalmology. The ocular intervention was identified using Taiwan reimbursement codes 31,32…”
Section: Methodsmentioning
confidence: 99%
“…Regarding comorbid psychiatric diseases, glaucoma has been shown to be associated with a higher risk of bipolar disease, major depressive disorders, and psychosis [ 13 ]. A review confirmed that glaucoma is more common in individuals with depression [ 14 ], even if a study published later found no increased risk of depression and anxiety in patients with glaucoma [ 15 ].…”
Section: Introductionmentioning
confidence: 99%